Plastic wound protectors decreased surgical site infections following laparoscopic-assisted colectomy for colorectal cancer: A retrospective cohort study. Issue 37 (September 2017) - Luo, Yang; Qiu, Yi-Er; Mu, Yi-Fei; Qin, Shao-Lan; Qi, Yang; Zhong, Ming; Yu, Min-Hao; Ma, Li-Ying
Abstract : Abstract: Laparoscopic surgery is widespread and safe for the management of patients with colorectal cancer (CRC). Although the use of standard surgical techniques can prevent perioperative wound infections, surgical site infections (SSIs) remain an unresolved complication in laparoscopic-assisted colectomy. The present study investigated the ability of plastic wound protectors applied to the extraction incision during the externalized portion of the procedure to reduce the rate of infection in laparoscopic-assisted colectomy. We completed a retrospective review of the medical records of patients who underwent nonemergent laparoscopic-assisted between January 2015 and June 2016. Outcomes for patients with and without the use of a wound protector were compared. A total of 109 patients were included in this study. There was 1 patient in the wound protector group (n = 57) and 7 in the nonwound protector group (n = 52) who developed a wound infection at the colon extraction site ( P  = .02). Furthermore, the average postoperative hospital stay in the wound protector group was shorter compared to the nonwound protector group (7.47 ± 0.24 vs 8.73 ± 0.54 days, P  = .03). In conclusion, this study indicates that the use of a plastic wound protector during laparoscope-assisted colectomy does reduce postoperative wound infection rates, and the wound protectors are beneficial for specimen extraction and digestive tract reconstruction.